Effects of Preoperative Chronic Steroid Use on Postoperative Outcomes in Orthopedic Surgery: A Systematic Review and Meta-Analysis - Yu-Ting Hung; Wei-Kai Hung; Ching-Chi Chi (MDPI AG, 2023)
Higher rates of postoperative complications have been found in preoperative chronic steroid users. However, the effects of preoperative chronic steroid use on outcomes in orthopedic surgery were unclear. We performed a systematic review of cohort studies examining the effects of chronic steroid use on postoperative outcomes following orthopedic surgery and searched PubMed, Embase, and CENTRAL through 29 April 2023. We included 17 studies with 1,546,562 patients. No increase in 30-day mortality (adjusted odds ratio (aOR) 1.40, 95% confidence interval (CI) 0.64-3.09) and composite thromboembolic events (aOR 1.61, 95% CI 0.99-2.63) but increases in 30-day overall complications (aOR 1.42, 95% CI 1.16-1.75), wound dehiscence (aOR 2.91, 95% CI 1.49-5.66), infectious complications (any infection (aOR 1.61, 95% CI 1.44-1.80), sepsis (aOR 2.07, 95% CI 1.34-3.21), superficial surgical site infection (SSI) (aOR 1.73, 95% CI 1.03-2.89) and deep SSI (aOR 1.96, 95% CI 1.26-3.05)), re-admission (aOR 1.62, 95% CI 1.48-1.77), both 30-day (aOR 1.28, 95% CI 1.03-1.59) and 1-year re-operation (aOR 1.78, 95% CI 1.09-2.92), pulmonary embolism (aOR 5.94, 95% CI 1.52-23.29), and deep vein thrombosis (aOR 2.07, 95% CI 1.24-3.46) were detected in preoperative steroid users. An increased risk of adverse outcomes following orthopedic surgery in chronic steroid users was found.